Hierarchical Event-Triggered Online Charging Management of Time-Varying Network of Electric Vehicles Based on Cooperative Game Theory - Maryam Amirabad Farahani; Mohammad Haeri (Majlesi Journal of Electrical Engineering)
This article reports on a method for detecting disconnection between electric vehicle parking lots during charge management and uncertainties and how to deal with these issues. In this study, each parking lots has an aggregator that can exchange information with other parking lot aggregators through a communication graph. A cyber-attack or communication failure may cause a problem in the connection between the aggregators and their information exchange. To detect the loss of contact between the aggregators or uncertainties, a method based on the mean field game is developed through a distributed consensus algorithm. Since the number of vehicles in every parking lot, power consumption and generation are uncertain, the smoothness of the network load curve is disrupted. so, in this work an online optimization based on receding horizon concept is proposed to monitor network load every hour. However, due to the complexity of online calculations and disconnection detection, the optimization is implemented in an event-based manner. Although several distributed event-triggered methods have been introduced recently, these methods generally require state estimators to calculate the event-triggered error, the latest states and the threshold which increases the computation cost. However, the proposed event-triggered control method only requires mean field game information to compute the event-triggered conditions and requires less computations. To have convergent game, a time-varying network topology is suggested when the communication of parking lots is lost and the disconnection event is triggered. To validate the effectiveness of our method, we conduct computer simulations that demonstrate their achievements.